Noah’s Ark: a saga of science denial - Robert M. Zink (Evolution: Education and Outreach)
Abstract The biblical story of Noah’s Ark sits at the intersection of faith and science. Over the years many have debated whether scientific evidence exists that would corroborate biological claims in the Ark narrative. Many religions have flood stories, but the biblical idea of a global flood that covered all land is factually erroneous, there is not enough water, and a global flood would turn all water saline, to the detriment of fresh-water organisms. The boat-building skills necessary for the Ark did not appear for centuries after the supposed flood. The notion that Noah took males and females of animals (plants were not mentioned), so as to not erase all of non-human creation, is biologically impossible given that there are 1.7 million species today, as well as undescribed and extinct species. To rescue the Ark narrative from this fatal flaw, creationists created a pseudo-scientific method called baraminology, which claims that animal “kinds” in the bible were not today’s species, but “common denominators” (baramins) from which today’s 1.7 million species arose (e.g., evolved, the antithesis of creation). Hence, Noah did not need to bring all species living at the time on the Ark, only a few baramins. The lack of mention of parasites, insects, microorganisms and much of the earth’s biodiversity (e.g., kangaroos) reveals the primitive stage of biological knowledge at the time. Recent claims that Noah had dinosaurs on the Ark, and that people co-existed with the 600 species of dinosaurs, including one as tall as a 6-story building, and predators like Velociraptor, lack scientific credibility. The idea that today’s species arose from a male and female baramin ignores inbreeding effects; matings would between siblings or siblings and parents. That Noah, his wife, three sons and their wives, gave rise to humanity also ignores inbreeding (and the effects of the parasites they carried). Attempts to reconcile biological aspects of the Ark narrative with modern understanding of geological and biological sciences require the denial of science and the substitution of faith. That is, those who believe in the biological accuracy of the Ark narrative have failed the burden of proof. Nonetheless, if someone wishes to derive a spiritual message from the story of Noah’s Ark, they can do so without requiring it to be scientifically factual, which is fortunate because it is not.